(untitled) (ENTHYMEMA, 2023)
Many of Primo Levi’s science-fiction stories crucially rely on playing with perspectives (juxtaposed, reversed, unnaturally reduced). A specific form of manipulation of perspective is offered by variations in scale. Through the narratological analysis of two science-fiction short stories – “Una stella tranquilla” and “Visto di lontano” –, this article explores the reading effects achieved by Levi by exploiting the notion of scale. It also considers how the tension between familiarity and estrangement, variously implemented, may shape views of reality and of our relationship with it. More specifically, it is suggested that playing with scale, while aiming to defamiliarize representation on the one hand, on the other it also points to the existence of deep correspondences between its various levels. The article also investigates how the role of experience, irreducibly embodied (that is to say, rooted in and developed through an undeniably human body), interacts with the management of variations in scale and estrangement effects.